Comparison of ultrasound imaging and video otoscopy with cross-sectional imaging for the diagnosis of canine otitis media. (November 2016) - Classen, J.; Bruehschwein, A.; Meyer-Lindenberg, A.; Mueller, R.S.
Highlights: Video otoscopy and ultrasound of the tympanic bulla were compared to CT. Ultrasound cannot replace CT in the diagnosis of canine otitis media. Video otoscopy is more reliable for the diagnosis of canine otitis media. Abstract: Ultrasound imaging (US) of the tympanic bulla (TB) for diagnosis of canine otitis media (OM) is less expensive and less invasive than cross-sectional imaging techniques including computed tomography (CT) and magnetic resonance imaging (MRI). Video otoscopy (VO) is used to clean inflamed ears. The objective of this study was to investigate the diagnostic value of US and VO in OM using cross-sectional imaging as the reference standard. Client owned dogs with clinical signs of OE and/or OM were recruited for the study. Physical, neurological, otoscopic and otic cytological examinations were performed on each dog and both TB were evaluated using US with an 8 MHz micro convex probe, cross-sectional imaging (CT or MRI) and VO. Of 32 dogs enrolled, 24 had chronic otitis externa (OE; five also had clinical signs of OM), four had acute OE without clinical signs of OM, and four had OM without OE. Ultrasound imaging was positive in three of 14 ears, with OM identified on cross-sectional imaging. One US was false positive. Sensitivity, specificity, positive and negative predictive values and accuracy of US were 21%, 98%, 75%, 81% and 81%, respectively. The corresponding values of VO were 91%, 98%, 91%, 98% and 97%, respectively. Video otoscopy could not identify OM in one case, while in another case, although the tympanum was ruptured, the CT was negative. Ultrasound imaging should not replace cross-sectional imaging for the diagnosis of canine OM, but can be helpful, and VO was much more reliable than US.